1988
DOI: 10.1073/pnas.85.4.1109
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila kinesin: characterization of microtubule motility and ATPase.

Abstract: Preparations of kinesin, a microtubule-based force-producing protein, have been isolated from Drosophila melanogaster embryos by incubation of microtubules with a nonhydrolyzable ATP analogue and gel filtration of proteins released from the microtubules by ATP. These preparations induced MgATP-dependent microtubule gliding in vitro with a Km for MgATP of 44 ,LM and a Vmax for gliding of 0.9 ,um/sec. Samples of Drosophila proteins that were active in motility assays possessed an average ATPase activity in solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 22 publications
4
59
1
Order By: Relevance
“…Protein A-or G-coated beads (Santa Cruz Biotechnology, Santa Cruz, CA) were added, and the suspensions were rocked overnight at 4°C and then washed three times with 500 l of extraction buffer and boiled in SDS-PAGE sample buffer. SDS-PAGE (7.5% gels), blotting, and staining were done as described previously (Saxton et al, 1988;Gertler et al, 1995), except that an ECL system was used for detection (Amersham, Piscataway, NJ). Primary antibodies used to detect Ena and Khc included rabbit anti-Khc R1.5 (Saxton et al, 1988) and rabbit anti-Ena-amino-terminal (Gertler et al, 1989), as well as the antibodies described above.…”
Section: Immunoprecipitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein A-or G-coated beads (Santa Cruz Biotechnology, Santa Cruz, CA) were added, and the suspensions were rocked overnight at 4°C and then washed three times with 500 l of extraction buffer and boiled in SDS-PAGE sample buffer. SDS-PAGE (7.5% gels), blotting, and staining were done as described previously (Saxton et al, 1988;Gertler et al, 1995), except that an ECL system was used for detection (Amersham, Piscataway, NJ). Primary antibodies used to detect Ena and Khc included rabbit anti-Khc R1.5 (Saxton et al, 1988) and rabbit anti-Ena-amino-terminal (Gertler et al, 1989), as well as the antibodies described above.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…SDS-PAGE (7.5% gels), blotting, and staining were done as described previously (Saxton et al, 1988;Gertler et al, 1995), except that an ECL system was used for detection (Amersham, Piscataway, NJ). Primary antibodies used to detect Ena and Khc included rabbit anti-Khc R1.5 (Saxton et al, 1988) and rabbit anti-Ena-amino-terminal (Gertler et al, 1989), as well as the antibodies described above. Prestained molecular weight standards were included in the SDS-PAGE, and their positions were marked on blots before blocking and antibody incubations.…”
Section: Immunoprecipitationmentioning
confidence: 99%
“…All Drosophila cells tested to date express KHC (Saxton et al, 1988). Tests of eye and wing discs by immunofluorescence (Golic and Lindquist, 1989;Golic, 1991;Xu and Rubin, 1993).…”
Section: Kinesin Is Dispensable For the Growth And Division Of Undiffmentioning
confidence: 99%
“…Conventional kinesin (often referred to below simply as kinesin) is a ubiquitous and abundant plus end-directed (Saxton et al, 1988;Hollenbeck, 1989). The majority of kinesin appears to be free in cytosol, but various studies have shown that it can associate with ER, vesicles, mitochondria, and other organelles (Hollenbeck, 1989;Pfister et al, 1989;Brady et al, 1990;Hirokawa et al, 1991;Houliston and Elinson, 1991;Wright et al, 1991;Leopold et al, 1992;Yu et al, 1992;Marks et al, 1994;Elluru et al, 1995; Okada et al, 1995;Sturmer and Baumann, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation